2005
DOI: 10.1128/jvi.79.22.14339-14345.2005
|View full text |Cite
|
Sign up to set email alerts
|

PrP TSE Distribution in a Primate Model of Variant, Sporadic, and Iatrogenic Creutzfeldt-Jakob Disease

Abstract: Human prion diseases, such as Creutzfeldt-Jakob disease (CJD), are neurodegenerative and fatal. Sporadic CJD (sCJD) can be transmitted between humans through medical procedures involving highly infected organs, such as the central nervous system. However, in variant CJD (vCJD), which is due to human contamination with the bovine spongiform encephalopathy (BSE) agent, lymphoreticular tissue also harbors the transmissible spongiform encephalopathy-associated prion protein (PrP TSE ), which poses a particularly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 33 publications
(38 reference statements)
6
53
1
2
Order By: Relevance
“…No specific background immunolabeling is detected in the optic nerve of a control animal immunostained with phosphate-buffered saline instead of the primary prion protein (PrP)-primary antibody using the TSA system (M). (Herzog et al 2005) were estimated to be 120 and 2500-10,000 times less, respectively, than the amounts present in brains. However, the proximal optic nerve of a vCJD patient contained extremely high levels of PrP Sc -only four times less than that found in the brain (Wadsworth et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…No specific background immunolabeling is detected in the optic nerve of a control animal immunostained with phosphate-buffered saline instead of the primary prion protein (PrP)-primary antibody using the TSA system (M). (Herzog et al 2005) were estimated to be 120 and 2500-10,000 times less, respectively, than the amounts present in brains. However, the proximal optic nerve of a vCJD patient contained extremely high levels of PrP Sc -only four times less than that found in the brain (Wadsworth et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies utilizing confocal microscopy confirmed an association between PrP RES and immune cells (FDCs, tingible body macrophages, and B cells) and extended the repertoire of prion diseases with lymphoid involvement to include CWD and vCJD (42,55,60,66,67). B cells have been associated with PrP RES transport and/or deposition within the lymphoid system (9,10,18,22,23,32,43,56,64,66,81). The present study supports this contention in demonstrating that MAb 2-104 ϩ primarily B cells harvested from peripheral blood or retropharyngeal lymph nodes contain sufficient infectious prions to transmit CWD to native or transgenic hosts.…”
Section: Interval To Detection Of Cwd Infection By Tonsil Biopsymentioning
confidence: 99%
“…Tissue preparation and purification of PrP Sc for gel electrophoresis PrP Sc purification of tissue was performed prior to western blot analysis as previously described (Bartz et al 2003(Bartz et al , 2005 with modifications based on the work of Herzog et al (2005). Briefly, tissues were weighed, minced with a razor blade, and mixed with digestion buffer (25 mM HEPES (pH 7 .…”
Section: Glucose Tolerance Tests -139h Scrapie-infected Hamstersmentioning
confidence: 99%